(untitled) (TAJ: Journal of Teachers Association, 2009)
We report a case of middle aged man who presented with stroke with right sided weakness. Later on, routine investigations reveal erythrocytosis on complete blood count and left renal mass on USG of abdomen. Further investigations correlate the above scenario with renal cell carcinoma. TAJ 2009; 22(1): 248-250